Characterisation of normal peripheral blood cells in cycle identified by monoclonal antibody Ki-67. Issue 3 (March 1992) - Cordone, I; Matutes, E; Catovsky, D
Abstract : AIMS: To investigate the numbers, morphology, and lineage assignment of Ki-67 positive cells in peripheral blood from normal subjects. METHODS: Single and double immunoenzymatic staining procedures, immunoperoxidase, and immunoalkaline phosphatase were used with Ki-67, a monoclonal antibody that recognises a nuclear antigen present in proliferating cells, with markers expressed in B and T lymphocytes and monocytes. RESULTS: In the five healthy donors 2.1% (range 1.6-3.7%) cells of the blood mononuclear fraction and 2.7% (range 2.3-3.9%) lymphocytes were Ki-67 positive. Of these, 88% (range 85-90%) were small cells and 12% (range 10-15%) were medium sized. Forty one per cent of the Ki-67 positive cells were CD3 positive by double immunoenzymatic staining and corresponded to T lymphocytes, and 11.4% were mature B cells expressing kappa or lambda light chains. Monocytes detected by the anti-lysozyme antibody were consistently Ki-67 negative. Half of the Ki-67 positive lymphocytes could not be accounted for by B or T cells with the markers used. Most Ki-67 positive cells were of small size; the B lymphocytes in cycle showed abundant cytoplasm and features suggestive of lymphoplasmacytic differentiation. CONCLUSIONS: The methodology described is useful for the simultaneous detection of nuclear and cytoplasmic antigens. The demonstration that a proportion of normal blood lymphocytes are in cell cycle raises the issue of whether immunophenotypic analysis of Ki-67 positive cells in haemopoietic malignancies with peripheral blood disease should be carried out to define more precisely the proportion of normal and neoplastic cells in cycle.